Synthesis and characterization of functionalized dihydropyrimidinones via one-pot isocyanide-based three-component reaction of N-formyl urea and dialkyl ACETYLENEDICARBOXYLATES - A. Naderi; B. Mohtat (Bulletin of the Chemical Society of Ethiopia, 2017)
The reactive intermediate generated by the addition of alkyl isocyanides to dialkyl acetylenedicarboxylates was trapped by N-formyl urea to produce highly functionalized dihydropyrimidinones in fairly good yields.